2019
DOI: 10.1002/jbm.a.36664
|View full text |Cite
|
Sign up to set email alerts
|

Halloysite nanotubes as tools to improve the actual challenge of fixed doses combinations in tuberculosis treatment

Abstract: Halloysite nanotubes (HLNTs) were used as nanocarriers of the tuberculostatic agent isoniazid (INH), a BCS (Biopharmaceutics Classification System) class III drug. Self‐assembling nanohybrids (INH‐loaded HLNTs) with an average outer diameter of 90 nm and polydispersity index of 0.7 approximately, were obtained by spontaneous adsorption of INH molecules to HLNTs powder in aqueous medium. The nanohybrids were aimed to improve oral drug bioavailability and reduce physicochemical incompatibility of INH with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 43 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…Recent publications have concluded that halloysite nanotubes enhances the permeability of drugs into cells improving the drug efficacy. 58,59 In Fig. 8(c) and (d), an increased in cell viability was observed for the inactivated Ag-TiO 2 samples.…”
Section: Drug Release Kinetic Studymentioning
confidence: 77%
See 1 more Smart Citation
“…Recent publications have concluded that halloysite nanotubes enhances the permeability of drugs into cells improving the drug efficacy. 58,59 In Fig. 8(c) and (d), an increased in cell viability was observed for the inactivated Ag-TiO 2 samples.…”
Section: Drug Release Kinetic Studymentioning
confidence: 77%
“…Recent publications have concluded that halloysite nanotubes enhances the permeability of drugs into cells improving the drug efficacy. 58,59…”
Section: Resultsmentioning
confidence: 99%
“…In vitro biocompatibility of clay minerals has been widely studied [ 15 , 96 , 97 , 98 , 99 ]. Some clay minerals have already been shown to have proliferating activity in cellular cultures, such as montmorillonite and halloysite [ 100 , 101 ]. Nonetheless, the induction of cellular proliferation by palygorskite clay mineral is a rare result [ 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the author's knowledge, different techniques and types of polymer/HNTs and their properties applied in the biomedical application have been recently reviewed. However, those reviews are limited to the HNTs' toxicity for drug delivery approaches 5,42,54,55 . Meanwhile, the authors believed that it is also essential to review the mechanical properties of polymer/HNTs nanocomposites in biomedical applications, as different applications such as human scaffolds, sutures, and implant plates require a different level of mechanical strength.…”
Section: Introductionmentioning
confidence: 99%